Trench curvature and deformation of the subducting lithosphere - Schettino, Antonio; Tassi, Luca (Geophysical journal international, 2012)
SUMMARY The subduction of oceanic lithosphere is generally accompanied by downdip and lateral deformation. The downdip component of strain is associated with external forces that are applied to the slab during its sinking, namely the gravitational force and the mantle resistance to penetration. Here, we present theoretical arguments showing that a tectonic plate is also subject to a predictable amount of lateral deformation as a consequence of its bending along an arcuate trench zone, independently from the long‐term physical processes that have determined the actual curvature of the subduction zone. In particular, we show that the state of lateral strain and the lateral strain rate of a subducting slab depend from geometric and kinematic parameters, such as trench curvature, dip function and subduction velocity. We also demonstrate that the relationship between the state of lateral strain in a subducting slab and the geometry of bending at the corresponding active margin implies a small component of lateral shortening at shallow depths, and may include large extensional lateral deformation at intermediate depths, whereas a state of lateral mechanical equilibrium can only represent a localized exception. Our formulation overcomes the flaws of the classic ‘ping‐pong ball’ model for the bending of the lithosphere at subduction zones, which lead to severe discrepancies with the observed geometry and style of deformation of the modern subducting slabs. A study of the geometry and seismicity of eight modern subduction zones is performed, to assess the validity of the theoretical relationship between trench curvature, slab dip function, and lateral strain rate. The strain pattern within the eight present‐day slabs, which is reconstructed through an analysis of Harvard CMT solutions, shows that tectonic plates cannot be considered as flexible‐inextensible spherical caps, whereas the lateral intraslab deformation which is accommodated through seismic slip can be explained in terms of deviations from the mechanical equilibrium.